L’impact du plomb sur le taux, la vitesse de germination et les paramètres anatomiques de Moringa oléifera L. - BELAIDI, Fatima Zohra; TAMERDJENT, Khadidja (My University, 2019)
Lead pollution has become a real problem threatening our ecosystems, with harmful effects on plant production and biodiversity, its presence at high doses causes several disruptions at all stages of plant development including germination. Moringa oleifera L is a plant species that grows in Asia and Africa, it has significant potential for water clarification and resistance to salt stress. The objective of this study is to evaluate the effect of lead in the form of lead nitrate (Pb(NO3)2) on the rate, rate of germination, and anatomy of the stem and root of Moringa oléifera L seeds. In this context, the seeds are put to germinate in kneading boxes containing two layers of filter paper soaked in increasing doses in Pb (0, 3, 5, 7 and 10 mM) applied at five repetitions by treatment, incubated in the dark in an oven set at 27°C for 15 days. At the end of the experiment and on the fifteenth day, cross-sections were made on the stems and roots of Moringa oleifera L. The results show that the effect of lead on the germination behaviour of Moringa oleifera L. is reflected in a non-significant decrease in the germination rate of stressed seeds compared to the control where it reaches 100% and in the germination rate in stressed seeds compared to the control. The anatomical structure of the treated roots and stems showed no significant anomalies compared to the control.
Keywords: Lead; Moringa oléifira L.; germination; rate and germination rate; Metal stress.